PENGARUH MOBILISASI MIKA MIKI TERHADAP PENINGKATAN PERISTALTIC TERHADAP PASIEN POST OP. APPENDIKTOMI DI KELAS III RSUD PROF. DR. SOEKANDAR MOJOSARI - Dwi w, Binarti (JURNAL KEPERAWATAN SEHAT, 2012)
ABSTRACTAppendisitis chaved of appendisitis which relative is often met able to arise without because clear or arise after Appendisitis obstruksi by faeces or effect its it him Mobilization early heel right and left represent an all important aspect at physiological function because that thing is esensial to maintain independence. Target of research know influence of mobilization early heel right and left to make-up of peristaltic of intestine at client of post appendictomy op in Room Operate On Class of III RSUD Prof. Dr. Soekandar Mojosari. Desain research of Pre experiment the used is one group pre test and post test design. Its population all client of post op appendictomy in Room Operate on Class III with amount of 14 people, technique sampling is purposive sampling and instrument the used is observation sheet. Statistical test of wilcoxon signed ranks test. Pursuant to result of wilcoxon signed ranks test ρ= 0,005 < 0,05 hence H1accepted or HOrefused by its meaning is influence of early mobilization heel right and left to make-up of peristaltic intestine at client of post op appendictomy in room operate on class III RSUD Prof. Dr.Soekandar Mojosari. Mobilization early give influence to mean cure of peristaltic of intestine that is the happening of make-up of the amount of peristaltic of intestine per minute after mobilization if compared to before mobilization. This matter show influence which enough is strong the than mobilization early to amount of peristaltik of intestine.Keyword: early mobilization, heel right and left, peristaltic of intestine, appendictomy